Alteration of CTCF-associated chromatin neighborhood inhibits TAL1-driven oncogenic transcription program and leukemogenesis. Issue 6 (22nd February 2020) - Li, Ying; Liao, Ziwei; Luo, Huacheng; Benyoucef, Aissa; Kang, Yuanyuan; Lai, Qian; Dovat, Sinisa; Miller, Barbara; Chepelev, Iouri; Li, Yangqiu; Zhao, Keji; Brand, Marjorie; et al.
Abstract: Aberrant activation of the TAL1 is associated with up to 60% of T-ALL cases and is involved in CTCF-mediated genome organization within the TAL1 locus, suggesting that CTCF boundary plays a pathogenic role in T-ALL. Here, we show that −31-Kb CTCF binding site ( −31CBS ) serves as chromatin boundary that defines topologically associating domain (TAD) and enhancer/promoter interaction required for TAL1 activation. Deleted or inverted −31CBS impairs TAL1 expression in a context-dependent manner. Deletion of −31CBS reduces chromatin accessibility and blocks long-range interaction between the +51 erythroid enhancer and TAL1 promoter-1 leading to inhibition of TAL1 expression in erythroid cells, but not T-ALL cells. However, in TAL1- expressing T-ALL cells, the leukemia-prone TAL1 promoter-IV specifically interacts with the +19 stem cell enhancer located 19 Kb downstream of TAL1 and this interaction is disrupted by the −31CBS inversion in T-ALL cells. Inversion of −31CBS in Jurkat cells alters chromatin accessibility, histone modifications and CTCF-mediated TAD leading to inhibition of TAL1 expression and TAL1-driven leukemogenesis. Thus, our data reveal that −31CBS acts as critical regulator to define +19- enhancer and the leukemic prone promoter IV interaction for TAL1 activation in T-ALL. Manipulation of CTCF boundary can alter TAL1 TAD and oncogenic transcription networks in leukemogenesis.